Art Education and Its Role In Developing Creativity, Building The Learner's Personality, and Achieving Quality Education - Elbatul Yousef Hammad (Journal of Scientific and Human Dimensions, 2026)
This article aims to highlight the importance of visual arts and their educational role in the learning process by clarifying the concept of art education and the integrative relationship.Between art and education, it also addresses the objectives of art education in schools and its role in fostering creativity and innovative thinking among leavers as well as the role of the art teacher in guiding artistic experiences and developing creative abilities the article.Emphases the contribution of art education to building students personalities and developing their psychological social and aesthetic aspects, in addition it discusses the importance of assessment in art education as a tool for improving learning outcomes in light of modern education in achieving quality education through diversifying teaching methods and promoting holistic learning.
Keywords: Art Education; Creativity Development; Character Building; Aesthetic Learning; Visual Thinking; Quality of Education; Educational Environment; Fine Arts